State-specific GluCEST alterations in insular subregions are associated with depression and plasma inflammatory biomarker levels in patients with inflammatory bowel disease - Lixue Xu; Jun Lu; Minsi Zhou; Haiyun Shi; Jing Zheng; Tianxin Cheng; Hui Xu; Dawei Yang; Xingwang Yong; Fang Xu; Chenyue Xu; Yan Dang; et al. (NeuroImage: Clinical)
Background: Depression commonly co-occurs with inflammatory bowel disease (IBD). Abnormal glutamate levels in the insula and altered plasma inflammatory biomarkers are observed in IBD and depression. However, the changes in glutamate concentrations in insular subregions in IBD and their relationship with depression and inflammatory markers remain unclear. This study aimed to investigate differences in glutamate concentrations in insular subregions between IBD patients and healthy controls (HCs) and their correlation with depression scores and inflammatory markers. Methods: Forty-two IBD patients (19 active, IBD-A; 23 in remission, IBD-R) and 46 HCs underwent glutamate chemical exchange saturation transfer (GluCEST) magnetic resonance imaging. Blood samples from 37 IBD patients were collected for plasma inflammatory biomarker analysis. GluCEST indices in insular subregions were measured. The Hospital Anxiety and Depression Scale (HADS-D) was used to estimate depression symptoms. Whole-brain voxel-based analysis using one-way ANOVA explored between-group differences in GluCEST indices within the insula. FDR-corrected partial correlation analysis evaluated the relationships between GluCEST, depression symptoms, and inflammatory factors. Results: GluCEST indices decreased in IBD patients in the left dorsal dysgranular subregion of the insula (dId) (uncorrected p < 0.001, cluster-level FWE-corrected p < 0.05). GluCEST indices in the left dId showed a significant positive correlation with HADS-D in IBD-R (FDR corrected q < 0.05). Additionally, GluCEST indices in the left dId were negatively correlated with CXCL9 (FDR corrected q < 0.05). Conclusion: State-specific GluCEST alterations in the left dId are a cerebral metabolic feature of IBD. These changes are associated with depression and inflammatory biomarkers, suggesting that the brain-immune-gut axis might underlie depression in IBD patients.